Whose Mental Model? Multi-stakeholder Most Advanced Yet Acceptable (MAYA) Visions of Disruptive Autonomous Maritime Technology - Rousi, Rebekah (Palgrave Macmillan, 2024)
Efforts to develop ship fleets and maritime traffic systems that take advance of artificial intelligence to operate without the direct guidance of humans have been on planning tables for decades. There are many challenges to removing humans from direct operation. Several are bound to human-specific abilities to sense and gauge changing conditions based on years of experience and tacit knowledge that accompanies expertise. It can be argued that the transition to autonomous shipping and maritime piloting may leave traffic vulnerable to the limitations of information technology developers. Moreover, considering initiatives to create disruptive innovation, this chapter argues that perhaps imaginings of an autonomous maritime are not only outdated but misleading and amateur from the perspective of maritime professionalism. This chapter re-positions humans within intelligent maritime developments, arguing that for truly disruptive innovation that exceeds fixated design typicality, designers need to delve into the mental models of maritime experts.
Keywords: Maritime piloting; Autonomous; Most Advanced yet Acceptable (MAYA); Design fixation; Human role; Mental models; Knowledge; Expertise; Yet Unknown but Better (YUBB); fi=Viestintätieteet|en=Communication Studies|